Lymphocyte Antigen 75 Polymorphisms Are Associated with Disease Susceptibility and Phenotype in Japanese Patients with Inflammatory Bowel Disease. (14th November 2016) - Hirayama, Atsuhiro; Joshita, Satoru; Kitahara, Kei; Mukawa, Kenji; Suga, Tomoaki; Umemura, Takeji; Tanaka, Eiji; Ota, Masao
Abstract : Recent genome-wide association studies have rapidly improved our understanding of the molecular pathways leading to inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC). Although several reports have demonstrated that gene single nucleotide polymorphisms (SNPs) are associated with susceptibility to IBD, its precise genetic factors have not been fully clarified. Here, we performed an association analysis between lymphocyte antigen 75 ( LY75 ) genetic variations and IBD susceptibility or phenotype. SNPs were genotyped in 51 CD patients, 94 UC patients, and 269 healthy controls of Japanese ethnicity. We detected a significant relationship with CD susceptibility for the rs16822581 LY75 SNP (P = 0.045 ). One haplotype (GT, P = 0.042 ) was also associated with CD susceptibility, while another carrying the opposite SNP (CA) was linked to an absence of surgical history for CD. Our findings confirm that LY75 is involved in CD susceptibility and may play a role in disease activity in the Japanese population.